Myanmar : Requests for Disbursement Under the Rapid Credit Facility and Purchase Under the Rapid Financing Instrument-Press Release; Staff Report; and Statement by the Executive Director for Myanmar. (IMF Staff Country Reports; Country Report ;, 2020)
The COVID-19 pandemic is expected to hit hard Myanmar's economy via weaker exports, tourism, remittances and domestic demand. The economic and social costs of a widespread outbreak could be large, against the backdrop of a frail healthcare system and inadequate social safety nets, as well as already low international reserves and a fragile banking system. The measures to contain and alleviate the effects of the pandemic open up sizeable BOP and fiscal financing gaps in the near term.